2016
DOI: 10.1155/2016/6492513
|View full text |Cite
|
Sign up to set email alerts
|

Central Retinal Artery Occlusion in Takayasu’s Arteritis as the First Presentation of the Disease

Abstract: Takayasu's arteritis (TA) is a chronic inflammatory granulomatous vasculitis which affects large and medium arterial vessels. The disease involves especially subclavian arteries and aortic branches but it can consist of any arteries. The major pathology is granulomatous panarteritis with intima proliferation and defects of the elastic lamina of the vessels. We present a case of central retinal artery occlusion in TA as the first presentation of the disease. To the best of our knowledge, the present case is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Noel et al (61) reported a case showing ocular aggravation in 2 months despite the combination of pulse MP and methotrexate, which stabilized after infliximab was added. The remaining 2 patients (one with the combination of pulse MP and methotrexate) became completely blind after treatments (46,55). The only patient diagnosed with RVO was treated with oral steroids and methotrexate, showing stabilized vision despite the occurrence of steroid-related glaucoma and cataract (61).…”
Section: Outcomes Of Medical Therapy Alonementioning
confidence: 99%
“…Noel et al (61) reported a case showing ocular aggravation in 2 months despite the combination of pulse MP and methotrexate, which stabilized after infliximab was added. The remaining 2 patients (one with the combination of pulse MP and methotrexate) became completely blind after treatments (46,55). The only patient diagnosed with RVO was treated with oral steroids and methotrexate, showing stabilized vision despite the occurrence of steroid-related glaucoma and cataract (61).…”
Section: Outcomes Of Medical Therapy Alonementioning
confidence: 99%
“…Vascular occlusion with ischemic changes[ 17 36 37 ] or as an isolated retinal finding has been described. [ 38 39 40 ] Analysis showed that out of 416 eyes, five had branch retinal artery occlusion (BRAO) (1.20%), two (0.48%) had branch retinal vein occlusion (BRVO), and 6 (1.44%) had central retinal artery occlusion (CRAO). There are two case reports[ 17 32 ] from India with BRAO in a 40-year-old lady and a 16-year-old girl with TA.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementary material 4 gives details of the studies included for analysis of various parameters. [ 2 3 5 6 7 8 11 12 13 14 15 17 18 19 20 26 29 30 31 32 33 34 35 36 38 39 40 41 42 44 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 65 66 68 69 70 71 72 74 75 76 77 78 83 84 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 ]…”
Section: Discussionmentioning
confidence: 99%
“…The most common ocular symptom is vision loss, but it is not unusual that the first symptoms of ocular ischemia are episodes of amaurosis fugax [4, 11]. Occlusive retinal vasculitis or retinal artery occlusions and ischemic optic neuropathy have been reported [7, 1214]. Cases of episcleritis and scleritis have also been described [15–18].…”
Section: Large Vessel Vasculitismentioning
confidence: 99%